Preparation of Thrombosis-targeted Lipid Microbubbles and Determination of Rabbit Carotid Artery Thrombosis by Microbubbles Ultrasonogaphy - 徐卫明 冯敏 赵洪洋 谢明星 黎维勇 符荣 (Journal of Huazhong University of Science and Technology. Medical sciences, 2013)
A kind of thrombus-targeted lipid-coated microbubbles were prepared, and the target prop- erty of the microbubbles and the effects of different methods detecting thrombosis in vessels were ob- served. Phospholipid-coated microbubbles were prepared by membrane-hydration method. Throm- bus-targeted lipid-coated fluorocarbon microbubbles were labeled with specific fluorescence and then integrated to the thrombus in vivo and ex vivo through an avidin biotin system. The thrombus was im- mediately observed for the distribution and property of the thrombus-targeted microbubbles under the optical microscope, fluorescence microscope and transmission electron microscope. The carotid throm- bosis models were set up in rabbits, and the effects of different methods detecting thrombosis in vessels were observed. The diameter of the phospholipid-coated microbubbles was 0.8-2.5μm, and even reached nanoscale in some of them. The zeta electric potential was about -11 mV and the concentration was about 1.08×10μmL. Immunofluorescence of rapid frozen sections in vivo and ex vivo showed that massive targeted lipid-coated microbubbles flocked around fresh blood clots and some aggregated within them under the light and fluorescence microscope. The number of aggregated microbubbles ex vivo was greater than that observed in the experiment in vivo, and the fluorescence observed in the ex- periment ex vivo was stronger than that in the experiment in vivo. The same imaging was observed un- der the electron microscope. Models of carotid thrombosis in rabbits were established successfully. Ef- fects of detecting thrombosis by means of thrombosis-targeted microbubble ultrasonoraphy and Sono Vue ultrasonography in vessels were more satisfactory than those by Color Doplor Flow Imaging （CDFI）, ordinary microbubbles and Three Dimensions-time of flight MR angiography （3D-TOF-MRA） （P〈0.01）. Compared to ordinary microbubbles ultrasonography, thrombosis-targeted microbubbles ultrasonography had the advantages whenever in imaging quality or in imaging time. Thrombus-targeted phospholipid-coated microbubbles were prepared successfully by membrane-hydration method. They could aggregate rapidly in fresh blood clots and enter deep into the internal part of the thrombus both in vivo and ex vivo, and had the targeted property of strongly conjugating with the thrombus. Compared to other thrombosis detection methods, ultrasonography with thrombosis-targeted microbubbles has obvious advantages in detecting thrombosis in vessels, mainly in： non-invasiveness, safety, good image quality, accuracy, and longer imaging time.